A case report of congenital Hemangiopericytoma as a buttock mass in a newborn - Y ZahedPasha (Babol University of Medical Sciences, 2001)
Objective: Hemangiopericytoma is a rare tumor with vascular origin with an incidence of only 10% among children. Along with the report of this rare condition, we reviewed literature. Case: A full term neonate with a birth weight appropriate to gestational age referred with a posterior midline buttock mass. The tumor was resected completely, the histopathologic and immunohistochemistry reaction showed hemangiopericytoma. Regular follow up examinations after discharge showed no recurrence at the location of resection and no remote metastasis up to 11 months of age. Conclusion: Hemangiopericytoma should be considered in differential diagnosis of posterior midline buttock mass in a neonate.